Fabrication of silastic testosterone enanthate implants to achieve virilizing levels of serum testosterone in swine - Nirvana Mahabir; Annie E. Newell-Fugate (MethodsX, 2024)
The aim of this study was to create a continuous drug delivery system that would yield serum testosterone levels in sexually mature, female pigs consistent with serum testosterone levels of human transgender men. Testosterone enanthate was mixed with medical grade silicone at a ratio of 20 % by weight, placed in silastic tubing to cure at room temperature for 24 h, then removed from the tubing mold and stored at 4 °C until surgical implantation. Testosterone enanthate oxidizes at high temperatures which is why the implants had to be stored cold. Each implant was 9 cm long and contained 0.56 g of testosterone enanthate. A minimum of one implant (0.56 g testosterone enanthate) and a maximum of four implants (2.24 g testosterone enanthate) were placed in the cervical subcutaneous fat of each pig. After implantation, serum testosterone was assessed over 40 days. Silastic testosterone enanthate implants increase serum testosterone and maintain it in a relatively constant state in a dose-dependent manner for ∼ 21–25 days post-implantation. • Effective method for subcutaneous delivery of large quantities of testosterone or testosterone metabolites in compact implants to large animal biomedical model species. • Maintains increased circulating testosterone levels for up to 3, 4 weeks post-implantation in pigs.